Prony Method Estimation as a New Approach for Surge Comparison Testing in Turn Insulation Diagnostics for Three Phase Stator Windings - Trujillo Guajardo, Luis Alonso; Rodríguez Alfaro, Luis Humberto; Rodríguez Maldonado, Johnny; González Vázquez, Mario Alberto; Salinas Salinas, Fernando; Shih, Meng Yen (Molecular Diversity Preservation International, 2023)
This article presents an evaluation of Prony method estimation and its implementation considerations for surge comparison test application in turn insulation diagnostics for three-phase stator windings. Surge testing diagnostics compares recorded surge voltage signals of motor winding, and a diagnostic is then defined with a defined value of EAR (error area ratio), which evaluates the difference between signals to determine a turn insulation diagnostic. First, an overview of surge testing is presented. Next, the Prony method and the considerations for its implementation in surge testing are described. Then, a numerical simulation is used to define a simulated turn fault surge voltage signal, where its parameters can be obtained with Prony method estimation and compared with EAR to evaluate its performance. Lastly, recorded surge test signals from two tested motors are used to validate Prony method estimation application for surge test diagnostics, where twelve recorded surge signals for no-fault and fault conditions were analyzed. The summary results of the surge signals parameter estimation are presented in the results and discussion section.